Verification, Induction, Termination Analysis Festschrift for Christoph Walther on the Occasion of His 60th Birthday - Siegler, Simon; Wasser, Nathan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This Festschrift volume, published in honor of Christoph Walther, contains contributions written by some of his colleagues, former students, and friends. In celebration of the 60th birthdays of Alejandro P. Buchmann, Sorin A. Huss and Christoph Walther, a colloquium was held on November 19th, 2010 in Darmstadt, Germany. The articles collected herein cover some of the main topics of Christoph Walther's research interests, such as formal modeling, theorem proving, induction, and termination analysis. Together they give a good overall perspective on the formal verification of the correctness of software systems.
Programming Inductive Proofs -- Termination Graphs for Java Bytecode -- Specifying and Verifying Organizational Security Properties in First-Order Logic -- Change Management for Heterogeneous Development Graphs -- The VATES-Diamond as a Verifier$1 (Bs Best Friend -- Dynamic Rippling, Middle-Out Reasoning and Lemma Discovery -- Verifying the Modal Logic Cube Is an Easy Task (For Higher-Order Automated Reasoners) -- Second-Order Programs with Preconditions.s
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Information systems; Artificial intelligence; Computer Science; Software Engineering; Computer Communication Networks; Logics and Meanings of Programs; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Information Systems Applications (incl.Internet).